Anthropogenic factors driving phosphorus contents in salto grande reservoir sediments, Săo Paulo state (se Brazil) / Influência antropogênica nas concentraçơes de fósforo dos sedimentos do reservatório de salto grande, estado de Săo Paulo (se Brasil) - Misailidis, Maria Laura (2018)
Phosphorus is an essential element for life and, when scarce, this macronutrient is a limiting factor for primary production. Phosphorus (P) is a widely used element in the composition of fertilizers, besides being present in large quantities in domestic effluents. Its accumulation in the springs is related to the proliferation of algae and cyanobacteria. In excess, P is a pollutant that contributes greatly to the eutrophication, development of reduced conditions and deterioration of water bodies. In order to understand how the anthropogenic action affected the accumulation of P in the freshwater reservoir of Salto Grande, Americana City (São Paulo State, Brazil), the evaluation of a temporal sedimentary record was carried out. For this purpose, a sediment core collected in the reservoir of Salto Grande was studied. The sediment core recorded the reservoir history since its filling in 1950. The comparison of P concentrations along the core with the population growth curve indicates that the population growth in the surrounding region has had a direct impact on the accumulation of P in the freshwater reservoir of Salto Grande. The eutrophication history of this major continental ecosystem of São Paulo State, was reflected by this sewage-derived from loading of P.